New methods for the management of gastric varices - Yoshida, Hiroshi (Baishideng Publishing Group Co., Limited, 2006)
Bleeding from gastric varices has been successfully treated by endoscopic modalities. Once the bleeding from the gastric varices is stabilized, endoscopic treatment and/or interventional radiology should be performed to eradicate varices completely. Partial splenic artery embolization is a supplemental treatment to prolong the obliteration of the veins feeding and/or draining the varices. The overall incidence of bleeding from gastric varices is lower than that from esophageal varices. No studies to date have definitively characterized the causal factors behind bleeding from gastric varices. The initial episodes of bleeding from esophageal varices or gastric varices without prior treatment may be at least partly triggered by a violation of the mucosal barrier overlying varices. This is especially likely in the case of varices of the fundus. In view of the high rate of hemostasis achieved among bleeding gastric varices, treatment should be administered in selective cases. Among untreated cases, steps to prevent gastric mucosal injury confer very important protection against gastric variceal bleeding.